Answer:
64
Step-by-step explanation:
the expression is
x² - 16x + _
the constant term is the square of the number residing with x divided by 2
the number number x = 16
therefore the constant term is (16/ 2)²
= 8²
= 64
the formula being used here is
(x + a)² = x² + 2ax + a²
Answer:
b
Step-by-step explanation:
when an reflected across the y axis only the x value changes and it changes negatively
Answer:
1.
-3x + 8y = -5
6x + 2y = -8
Set the equations to a common variable.
-3x + 8y = -5 → 8y = 3x - 5 → y = 3/8x - 5/8
6x + 2y = -8 → 2y = -6x - 8 → y = -3x - 4
Set the equations equal to each other.
3/8x - 5/8 = -3x - 4
Combine like terms.
3x + 3/8x = -4 + 5/8
3.375x = -3.375
Divide by 3.375
x = -1
Plug x back in to find y.
-3x + 8y = -5
-3(-1) + 8y = -5
3 + 8y = -5
8y = -8
y = -1
answer: (-1, -1)
2.
3x + 2y = -16
-3x - 8y = 46
Set the equations to a common variable.
3x + 2y = -16 → 2y = -3x - 16 → y = -3/2x - 8
-3x - 8y = 46 → -8y = 3x + 46 → y = -3/8x - 23/4
Set the equations equal to each other.
-3/2x - 8 = -3/8x - 23/4
Combine like terms.
-9/8x = 9/4
or
-1.125x = 2.25
Divide by -1.125
x = -2
Plug x back in to find y.
3(-2) + 2y = -16
-6 + 2y = -16
2y = -10
y = -5
answer: (-2, -5)
3,-4 is the correct anwser
Answer:
50.714 (3 dp)
Step-by-step explanation:
Using trigonometry.
![cos(\theta)=\frac{adj}{hyp} \\adj = hyp * cos(\theta)\\120*cos(65) = 50.714](https://tex.z-dn.net/?f=cos%28%5Ctheta%29%3D%5Cfrac%7Badj%7D%7Bhyp%7D%20%5C%5Cadj%20%3D%20hyp%20%20%2A%20cos%28%5Ctheta%29%5C%5C120%2Acos%2865%29%20%3D%2050.714)